Does Leaders' Health (and Work-Related Experiences) Affect their Evaluation of Followers' Stress? - Gabriele Giorgi; Serena Mancuso; Francisco Javier Fiz Perez; Francesco Montani; Francois Courcy; Giulio Arcangeli (Elsevier, 2015)
Background: Stressed workers suffer from severe health problems which appear to have increased. Poor leadership is especially considered a source of stress. Indeed, supervisors might perceive their subordinates to be similar to them as far as stress is concerned and this might more widespread in organizations than previously thought. Methods: The present research investigates the relationships between leaders' health, in terms of work-related stress, mental health, and workplace bullying and their evaluation of subordinates' stress. Five regression models were formulated to test our hypothesis. This is a cross-sectional study among 261 Italian leaders, using supervisor self-assessment and leaders' assessments of their subordinates. Results: Leaders' health was related to their evaluation of staff stress. Job demand, lack of job control, and lack of support by colleagues and supervisors evaluated in their subordinates were particularly associated with the leaders' own health. Conclusion: Implications for developing healthy leaders are finally discussed.